INVESTIGATION OF BLOCKING ALGORITHM FOR TRANSFORMER CURRENT PROTECTIONS IN MAGNETIZING INRUSH CURRENT MODES - A. N. Kuzovlev; V. V. Moroz; A. M. Golubev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Presents investigations on blocking  algorithm for transformer  current  protections  during magnetizing  inrush  current. The investigations have shown that the algorithm has high sensitivity and reliably determines magnetizing  inrush current modes.